Pengadaan Tanah Untuk Kepentingan Umum (Perbandingan antara Malaysia dan Indonesia) - mukmin zakie (Jurnal Hukum IUS QUIA IUSTUM, 2011)
Land is a basic capital for human’s life. As a basic capital, land has two functions: productive function and non-productive function. The needs of land use often clashed with each other since the amount of land is limited, in other side population grows rapidly. For the sake of development, every state in the world needs land. The development is related to land and needs land. During the practice of development, the program might clashed with the land which right already attributed or the land has already been possessed by person or legal entity. As the strategy to obtain that land, government uses the term of public interest. This research is a comparative research between Indonesia and Malaysia in providing land for public interest. The problem in this research is how the regulation take over the land and the concept of public interest in Indonesia and Malaysia.The result of the research shows that there is deviation of the meaning of public interest in both state which generates different perception in society related to land providing. Even so, land providing for public interest has already expressed into legislation in both states.